1992
DOI: 10.1021/ac00036a007
|View full text |Cite
|
Sign up to set email alerts
|

Planar chromatography

Abstract: Jo*eph Sherma received a B.S. In chemistry from Upsala College, East Orange. NJ. In 1955 and a Ph D. in analytical chemistry from Rudgers University in 1958. His thesis research In Ion exchange chromatography was under the direction of the late Wm. Rieman III. Dr. Sherma joined the faculty of Lafayette College in Sept 1958 and Is presently John D. & Frances H. Larkin Professor and Head of the Department of Chemistry and Is in charge of three courses in analytical chemistry. Dr. Sherma independently and with ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…[20] In human organisms, aromatic acids are synthesized as metabolites in intoxication by toluene, xylene, and ethyl benzene. [20] In human organisms, aromatic acids are synthesized as metabolites in intoxication by toluene, xylene, and ethyl benzene.…”
Section: Various Organic Compoundsmentioning
confidence: 99%
“…[20] In human organisms, aromatic acids are synthesized as metabolites in intoxication by toluene, xylene, and ethyl benzene. [20] In human organisms, aromatic acids are synthesized as metabolites in intoxication by toluene, xylene, and ethyl benzene.…”
Section: Various Organic Compoundsmentioning
confidence: 99%
“…But the separation and extraction of the active components in TCMs are tedious and inefficient because of their complicated matrix and the poor selectivity of conventional separation materials. Much research has been reported to achieve selective interaction with the target molecule by changing the sorption materials [11]. Recently, it has attracted considerable attention that the MIPs were applied as separation materials to extract desired active components directly from the TCMs [12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…It is very difficult to separate them effectively. Thus, much research has been directed toward the variation of the sorption materials to achieve the selective interaction with the target molecule 33…”
Section: Introductionmentioning
confidence: 99%